2020
DOI: 10.1111/cts.12764
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Generalizability Assessment in the Big Data Era: A Review

Abstract: Clinical studies, especially randomized, controlled trials, are essential for generating evidence for clinical practice. However, generalizability is a long‐standing concern when applying trial results to real‐world patients. Generalizability assessment is thus important, nevertheless, not consistently practiced. We performed a systematic review to understand the practice of generalizability assessment. We identified 187 relevant articles and systematically organized these studies in a taxonomy with three dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 61 publications
1
68
0
Order By: Relevance
“…patients. As results of COVID-19 studies become available, we will be able to assess the extent to which the trial design and eligibility criteria in particular would impact the findings as well as the real-world population representativeness of these studies using generalizability assessment methods [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…patients. As results of COVID-19 studies become available, we will be able to assess the extent to which the trial design and eligibility criteria in particular would impact the findings as well as the real-world population representativeness of these studies using generalizability assessment methods [6].…”
Section: Discussionmentioning
confidence: 99%
“…In future work, we will perform a longitudinal analysis of COVID-19 studies to assess the changes in the use of eligibility criteria and consideration of risk factors for severe illness in COVID-19 patients. As results of COVID-19 studies become available, we will be able to assess the extent to which the trial design and eligibility criteria in particular would impact the findings as well as the real-world population representativeness of these studies using generalizability assessment methods [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a number of methods and tools have been developed to quantify clinical trials' population representativeness (or generalizability). 9 These methods can be categorized into two major approaches: (1) sample-driven and often called a posterior generalizability, where these methods measure the representativeness the study samples (i.e., participants enrolled in clinical trials) over the target population, and (2) eligibility-driven and called a priori a Qian Li, MS and Yi Guo, PhD contributed equally, co-first authors b Corresponding: Jiang Bian, PhD; bianjiang@ufl.edu generalizability, where these methods measure the representativeness of the study population (i.e., patients who met the eligibility criteria) over the target population. 10 Although the a posterior generalizability is important, it cannot be changed after the fact as the trial has already been concluded.…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, more than 70% of clinical trial generalizability assessment studies reported low generalizability of completed trials, partly due to low enrollment. 17 The rapid growth of the electronic health records (EHR) provides an unprecedented opportunity to harness its data to full potential for secondary use. 18 Moreover, the last few years have also witnessed an increasing number of clinical research networks focused on building large collections of data from EHRs and claims to provide cohort discovery services.…”
Section: Introductionmentioning
confidence: 99%